Managing transitions making the most of change - Bridges, William (Philadelphia, Pa Da Capo Press, 2009)
From the most trusted voice on transition, a thoroughly updated and expanded edition of the classic guide to dealing with the human side of organizational change. Directed at managers and employees alike in today s business world where constant change is the norm and mergers, redundancy, bankruptcy and re-structurng have become common phenomena. Managing Transitions addresses the fact that it is people that have to embrace a new situation and carry out the corresponding changes.
Includes bibliographical references and index.
Keywords: Organizational change--Management.Industrial management